Crítica literária Machadiana: recepções contemporâneas - COSTA, Rita de Cássia Bastos Cirqueira (2018)
Considering Machado de Assis's work and observing the critical analysis focused on the writer, especially the one developed contemporaneously, we ask the question: how to critique criticism? How to find more than one author without incurring the "most of the same", seeking in his critics the possible answers to what is questioned in his work? Considering all this, we believe that it is possible to rethink Machado's literature, based on critique about his work, which makes possible a new accommodation of the author's text in contemporary space. Therefore, this research studies two critical productions currently written: The problem of the realism of Machado de Assis and Machado de Assis: for a poetics of emulation, produced by Gustavo Bernardo Krause and João de Cezar Castro Rocha, respectively. Initially, this research opens a discussion about the place of Brazilian criticism (Nunes, 2009) (JOBIM, 2012), as well as about its current form of production. Next, we develop a reflection on the importance of Machado de Assis and the reason for his canonization in Brazilian literature (GUIMARÃES, 2017). The last part of the research is devoted to its corpus of analysis. The discussion of the critical reception of Machado de Assis, demarcating it within the contemporary debate, may enable Machado de Assis's readers to gain a broader understanding of his work. Thus, this research intends to be a space for cataloging and discussion about how these critiques have been produced in Brazil.